Mechanisms of seasonal reproduction in cattle - Zeebaree, Bayar (2016)
This study was conducted to evaluate the effect of season on reproductive parameters in cattle in the temperate climate of the UK. In the first study, reproductive fertility data were collected from a local dairy herd. The results revealed that cows born in autumn were inseminated at an earlier age (P<0.05) and calved earlier (P<0.001) than spring and summer born animals. In addition, the conception rate within 90 days after calving was higher (P<0.05) in autumn calving animals. Conception rate was higher (P<0.05) when insemination was performed at a temperature range from 7 to 15°C compared with <7 and >15°C and a temperature humidity index (THI) range from 40 to 59 compared with >60 units (10 days before and 21 days after insemination). In the second study, ovarian tissues were collected from a local abattoir to investigate the effect of season on follicular populations, corpus luteum (CL) development and incidence of multiple ovulations. There were no effects of season on antral follicle count. However, individual and total CL weight was heavier in the autumn. Additionally, season influenced multiple ovulations with a higher incidence (P<0.05) in summer and autumn compared to winter and spring. The number of follicles >7mm in cows with multiple CLs was higher (P<0.05) than cows with a single CL. The individual CL weight was heavier in single ovulation cows. However, the total luteal tissue weight and total progesterone (P4) content of luteal tissue was higher in cows with multiple ovulations. The third study investigated the effects of culturing granulosa cells (GCs) under low (5%; physiological oxygen (O2)) conditions rather than traditional culture (20%; atmospheric O2) systems. Granulosa cells from antral follicles were cultured in fibronectin coated plates in M199 for up to 144 hour (h) under physiological (5%) and atmospheric (20%) O2 tension. Melatonin was added at one of four concentrations (0, 20, 200, 2000 pg/ml). The number of viable GCs was greater (P<0.05) under 5% O2 than 20% O2. Reactive oxygen species (ROS) generation was similar under both physiological and atmospheric O2, but was reduced (P<0.05) by treatment with melatonin. Oestrogen concentration (P<0.001) and aromatase activity (P<0.014) were also influenced by O2 tension in a time dependent manner. Both oestradiol (E2) production and aromatase enzyme activity were maintained for up to 144 h of culture under 5% O2 conditions. Progesterone production was increased under 20% O2 compared with 5% O2 (P<0.05). Additionally, the expression of hydroxy-delta-5-steroid dehydrogenase, 3 beta- and steroid delta-isomerase 1 (HSD3B1) mRNA increased (P<0.05) with time under 20% O2, but remained unchanged at 5% O2. Haemoglobin subunit alpha 1 (HBA) transcript was increased (P<0.05) under 5% O2 levels. The final study quantified the effect of temperature and melatonin on GC function. Cells were cultured for up to 144 h under 5% O2 tension. Treatments commenced after 48 h of culture and consisted of two incubation temperatures (37.5 vs 40.0°C) and four melatonin treatments. Melatonin increased cell number at high temperature (40.0°C). However, BCL2-associated X protein (BAX) mRNA expression was greater (P<0.05) in GCs cultured at 40.0°C than at 37.5°C by 144 h. Culture temperature did not affect ROS, but melatonin reduced (P<0.001) generation of ROS. Oestradiol production increased with time (P<0.001) and was not affected by temperature. In contrast, high temperature reduced P4 production (P<0.001) at 144 h of culture. Similarly, the effect of melatonin treatment depended on temperature; melatonin increased P4 production at 37.5C, while reducing P4 at 40.0C. Temperature increased acetylserotonin O-methyltransferase (ASMT) mRNA expression (P<0.05) though there was no significant effect of temperature and melatonin on tumour protein p53 (P53), HSD3B1, superoxide dismutase (SOD1 and SOD2), HBA and heat shock protein family A (Hsp70) member 1A (HSPA1A) gene expression. The results of this thesis contribute to our understanding of the effects of season on ovarian function and seasonal variation in cattle fertility particular in temperate climate regions where season influenced puberty, conception rate, incidence of multiple ovulations and CL development. In in vitro studies, low O2 (5%) enhance cell proliferation, reduced luteinisation and altered steroidogenesis as well as increasing the expression of HBA mRNA. Culture at higher temperature reduced P4 production and increased apoptotic mRNA while addition of melatonin reduced ROS generation and influenced P4 production. This new approach to culture could offer a valuable system for future investigation of the physiological function of cells in vitro.